1996
DOI: 10.1007/bf03011809
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and awareness with recall during total intravenous anaesthesia

Abstract: Purpose: A double-blind study was undertaken to evaluate the influence of graded doses of midazolam on propofol infusion requirements, recovery characteristics and the quality of recovery, associated with propofol/alfentanil/02 total intravenous anaesthesia (TIVA ).Methods: Ninety ASA Class I and II subjects scheduled for arthroscopic knee surgery were randomly allocated to receive either placebo (Group PLAC), or midazolam doses of 15, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…Despite relatively high BIS values, none of our patients complained of awareness, which is consistent with the results of other studies in which no patients complained of awareness during anesthesia with midazolam and fentanyl for a coronary artery bypass graft, even when the BIS was [60 [10]. Other studies have also shown that the incidence of intraoperative awareness is lower in patients receiving midazolam before the induction of general anesthesia than in those who do not receive it [22,23], suggesting that midazolam has a good amnesic effect and ability to prevent intraoperative awareness. However, we cannot completely eliminate the possibility that intraoperative awareness did occur.…”
Section: Discussionsupporting
confidence: 93%
“…Despite relatively high BIS values, none of our patients complained of awareness, which is consistent with the results of other studies in which no patients complained of awareness during anesthesia with midazolam and fentanyl for a coronary artery bypass graft, even when the BIS was [60 [10]. Other studies have also shown that the incidence of intraoperative awareness is lower in patients receiving midazolam before the induction of general anesthesia than in those who do not receive it [22,23], suggesting that midazolam has a good amnesic effect and ability to prevent intraoperative awareness. However, we cannot completely eliminate the possibility that intraoperative awareness did occur.…”
Section: Discussionsupporting
confidence: 93%
“…[14] There is also evidence that TIVA may predispose patients to awareness compared to inhalational anesthetics with measurement of ETAC. [2491516] In addition, there has been speculation about the influence of genetics and ethnic differences on anesthetic requirements; this may have also contributed to the low incidence of awareness in our study as compared to western population. [517]…”
Section: Discussionmentioning
confidence: 96%
“…18,19 Furthermore, commonly used TIVA combinations such as propofolremifentanil or propofol-alfentanil show less haemodynamic stability compared with inhaled drugs. 20 For these reasons, we prefer to use combined anaesthesia with inhalational (sevoflurane) and intravenous (i.v.…”
Section: Anaesthetic Technique and Ponvmentioning
confidence: 99%